Prevalence naturally infected gastrointestinal parasites and complete blood count condition on Wonosobo sheep at Wonosobo District, Central Java, Indonesia - Zein Baihaqi; WISNU NURCAHYO; IRKHAM WIDIYONO (Society for Indonesian Biodiversity, 2020)
Abstract. Baihaqi ZA, Nurcahyo W, Widiyono I. 2020. Prevalence naturally infected gastrointestinal parasites and complete blood count condition on Wonosobo sheep at Wonosobo District, Central Java, Indonesia. Biodiversitas 21: 3057-3061. The aim of this study was to determine complete blood count of Wonosobo sheep infected with internal parasites on sheep farms in Wonosobo District, Central Java, Indonesia. Fecal and blood samples were taken from 130 female Wonosobo sheep. Fecal samples were individual and the numbers of worm eggs per gram of feces (eggs per gram, EPG) were counted. Complete blood count analyzed with a hematology analyzer machine and total protein were measured with a refractometer. The total average prevalence of gastrointestinal (GI) parasite infections in the Wonosobo sheep are 66.92%. The prevalences of low EPG and high EPG GI parasite infections in female Wonosobo sheep were 19.23% and 47.69%. The gastrointestinal worm species found infecting female Wonosobo sheep in this study were Haemonchus spp., Ostertagia spp., Trichostrongylus spp., Trichuris spp., Bunostomum spp., and Moniezia spp. The most prevalent GI parasites infections in  Wonosobo sheep were caused by Haemonchus spp., and the last prevalent ones were caused by Trichuris spp. Mean Corpuscular Volume (MCV), Mean Corpuscular Hb (MCH), Mean Corpuscular Hb Concentration (MCHC), White Blood Cell (WBC), neutrophil, eosinophil, and lymphocyte counts in female Wonosobo sheep with naturally occurring gastrointestinal worms that had EPG > 600 were significantly higher (p < 0.001) than those in sheep that had EPG <600. Hb, Hematocrit (HCT), Red Blood Cell (RBC), and Total Protein (TP) were significantly lower (p < 0.001) in sheep with EPG values >600 than in sheep with EPG <600. Monocyte and basophil values were not significantly different (p > 0.05) between infected sheep with EPG <600 and those with EPG >600. This study shows that gastrointestinal worm infections naturally affect the hematology and blood chemistry of female Wonosobo sheep in Wonosobo district, Central Java, Indonesia.